Medios tecnológicos digitales y la comunicación oral en niños de la Institución Educativa Inicial N°160 Mi Primer Aprendizaje, Caballococha 2024 - Perez Icomena, Etti Anali (2024)
The purpose of the research was to determine the relationship between the level of use of digital technological media and oral communication in children of the Institución Educativa Inicial N°160 Mi Primer Economía Caballococha 2024. In this study, a quantitative approach was used, the type of research was relational with a non-experimental design, characterized by a correlational and transectional design. The population was made up of 79 children from the Initial Educational Institution No. 160 My First Learning Caballococha 2024, observation was used as a technique, and an observation guide was used as an instrument for data collection that was validated by three experts in the field. The results obtained were, Spearman's correlation coefficient (ρρρ) between "Oral Communication" and "Digital Technological Media" is 0.632; bilateral significance (p-value) of 0.05, reaching the conclusion that there is a positive relationship between the use of digital technological media and oral communication in the children evaluated.